2019
DOI: 10.3390/electronics8050578
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis to Predict End-to-End Quality of Wireless Community Networks

Abstract: Community Networks have been around us for decades being initially deployed in the USA and Europe. They were designed by individuals to provide open and free “do it yourself” Internet access to other individuals in the same community and geographic area. In recent years, they have evolved as a viable solution to provide Internet access in developing countries and rural areas. Their social impact is measurable, as the community is provided with the right and opportunity of communication. Community networks comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Recently, time-series analysis has been considered to estimate link quality (LQ) and end-to-end quality (EtEQ) in the routing layer, involving real-world wireless mesh community networks. For instance, Millan et al [19][20][21][22] shown that time-series analysis can be used to improve the performance of the routing protocol, by providing information that allows making appropriate and timely decisions. This contributes to maximize the message delivery rate and minimize traffic congestion at both levels (i.e., LQ and EtEQ) with a small average mean absolute error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, time-series analysis has been considered to estimate link quality (LQ) and end-to-end quality (EtEQ) in the routing layer, involving real-world wireless mesh community networks. For instance, Millan et al [19][20][21][22] shown that time-series analysis can be used to improve the performance of the routing protocol, by providing information that allows making appropriate and timely decisions. This contributes to maximize the message delivery rate and minimize traffic congestion at both levels (i.e., LQ and EtEQ) with a small average mean absolute error.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of predictors increases the complexity of the routing protocols, because of the additional hardware and software required to make and validate predictions. Moreover, penalty mechanisms are usually introduced to the system when there is a high rate of mispredictions, which negatively affect the performance of these protocols.Prediction mechanisms have been embedded in routing protocols to foresee several aspects of a network, such as nodes mobility [13], reliability of its topology [14,15] and quality of links and end-to-end paths [16][17][18][19][20][21][22][23][24]. These mechanisms have also been used to reach particular communication…”
mentioning
confidence: 99%
“…End-to-end quality of wireless community networks [16] Individuals create community networks to provide free Internet access. End-to-end quality (EtEQ) tracking is used by link-state routing systems to pick pathways that maximize delivery rate while minimizing traffic congestion.…”
mentioning
confidence: 99%